MEDIA PEMBELAJARAN BAHASA INGGRIS BERBASIS TIK â€œDAILY ACTIVITYâ€ TINGKAT SMP - Riswan - (JURNAL AKADEMIKA)
The development of information technology to change the paradigm of learning process of Teacher Centered Learning (TCL) to the Student Center Learning (SCL), the role of the teacher is no longer dominant in learning, students become active part in establishing themselves in learning (constructivism), of learning membosan, because teachers learning can not pack well into learning fun, learning can be done anywhere and anytime, internet technology has become an intermediary students to study e-learning to understand the subject matter, learning English is used very intimidating for students as well as lessons mathematics, is now a very enjoyable lesson, because it has been packed with the advantages of Information and Communication Technology (ICT) based e-learning, as was done in the creation of e-learning is learning English with daily material activity in SMP